PENGARUH STATUS PARTISIPASI DALAM PELAYANAN KESEHATAN DASAR (POSYANDU) TERHADAP STATUS GIZI BALITA DI PONKESDES MLAJAH BANGKALAN - Alis Nur Diana; Lelly Aprilia Vidayati; Siti Rochimatul Lailiyah (Rena Cipta Mandiri, 2025)
Nutritional status describes the body's condition resulting from food intake and nutrient use, which is vital for energy, growth, tissue repair, and physiological function. A preliminary study at Ponkesdes Mlajah Bangkalan found that among 10 mothers with toddlers suffering from poor nutrition, 80% of the children did not actively attend the posyandu, while 20% did. This study aimed to examine the effect of participation in basic health services (posyandu) on toddlers’ nutritional status. Using an observational analytic design with a cross-sectional approach, 143 respondents (from 227) were selected through Stratified Simple Random Sampling. The independent variable was posyandu participation status; the dependent variable was toddler nutritional status. Data were collected using Islamic boarding school cohort records and Z-score applications, and analyzed using the Spearman Rank test (Ethics No: 1586/KEPK/STIKES-NHM/EC/II/2024). Findings showed 62.2% of respondents were inactive in posyandu, while 66.4% of toddlers had normal nutritional status. With a p-value of 0.094 (ρ > α = 0.05), the result indicated no significant influence. Recommendation: Parents should be encouraged to attend posyandu regularly, aided by cadres through reminders and nutrition education efforts.